2011
DOI: 10.2146/ajhp100300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an approach to improving the adoption rate of wireless drug library updates for smart pumps

Abstract: A multidisciplinary team actively engaged in the updating of wireless i.v. smart pump drug libraries reduced the amount of time required to reach a goal adoption rate of 80%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…23 Research has shown that it may take days or even weeks for the new drug library to be installed on all smart infusion pumps within a hospital. [24][25][26] Using an out-of-date drug library on a smart pump can lead to medication errors due to incorrect drug dosing limits. 27 Although a smart pump can still function normally without an updated drug library, there may be negative consequences for not using the most current library.…”
Section: Stakeholder Perceptions Of Smart Infusion Pumps and Drug Libmentioning
confidence: 99%
“…23 Research has shown that it may take days or even weeks for the new drug library to be installed on all smart infusion pumps within a hospital. [24][25][26] Using an out-of-date drug library on a smart pump can lead to medication errors due to incorrect drug dosing limits. 27 Although a smart pump can still function normally without an updated drug library, there may be negative consequences for not using the most current library.…”
Section: Stakeholder Perceptions Of Smart Infusion Pumps and Drug Libmentioning
confidence: 99%
“…Updating the drug library has been identified as an area of improvement with regard to determining when the update will occur and increasing communication. 9 Where an organization is with implementation may affect how often you update your drug library. See Table 1 for Smart Pump Implementation Checklist.…”
Section: Drug Librarymentioning
confidence: 99%